Engineering the methylotrophic yeast Ogataea polymorpha for lactate production from methanol - Wefelmeier, Katrin; Schmitz, Simone; Haut, Anna Maria; Otten, Johannes; Jülich, Tobias; Blank, Lars Mathias (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Lactate has gained increasing attention as a platform chemical, particularly for the production of the bioplastic poly-lactic acid (PLA). While current microbial lactate production processes primarily rely on the use of sugars as carbon sources, it is possible to envision a future where lactate can be produced from sustainable, non-food substrates. Methanol could be such a potential substrate, as it can be produced by (electro)chemical hydrogenation from CO2. Methods: In this study, the use of the methylotrophic yeast Ogataea polymorpha as a host organism for lactate production from methanol was explored. To enable lactate production in Ogataea polymorpha, four different lactate dehydrogenases were expressed under the control of the methanol-inducible MOX promoter. The L-lactate dehydrogenase of Lactobacillus helveticus performed well in the yeast, and the lactate production of this engineered strain could additionally be improved by conducting methanol fed-batch experiments in shake flasks. Further, the impact of different nitrogen sources and the resulting pH levels on production was examined more closely. In order to increase methanol assimilation of the lactate-producing strain, an adaptive laboratory evolution experiment was performed. Results and Discussion: The growth rate of the lactate-producing strain on methanol was increased by 55%, while at the same time lactate production was preserved. The highest lactate titer of 3.8 g/L in this study was obtained by cultivating this evolved strain in a methanol fed-batch experiment in shake flasks with urea as nitrogen source. This study provides a proof of principle that Ogataea polymorpha is a suitable host organism for the production of lactate using methanol as carbon source. In addition, it offers guidance for the engineering of methylotrophic organisms that produce platform chemicals from CO2-derived substrates. With reduced land use, this technology will promote the development of a sustainable industrial biotechnology in the future.